2012
DOI: 10.1021/jp2119263
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Molecular Rotors Confined in Two Dimensions: Transition from a 2D Rotational Glass to a 2D Rotational Fluid in a Periodic Mesoporous Organosilica

Abstract: The motional behavior of p-phenylene-d(4) rotators confined within the 2D layers of a hierarchically ordered periodic mesoporous p-divinylbenzenesilica has been elucidated to evaluate the effects of reduced dimensionality on the engineered dynamics of artificial molecular machines. The hybrid mesoporous material, characterized by a honeycomb lattice structure, has arrays of alternating p-divinylbenzene rotors and siloxane layers forming the molecularly ordered walls of the mesoscopic channels. The p-divinylben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 103 publications
2
39
0
Order By: Relevance
“…For example, when exploring the temperature-dependence of the rotational dynamics of a p -phenylene group in a periodic mesoporous organosilicate (PMO), we obtained non-linear data within a temperature region indicating an apparent activation energy of 47 kcal/mol and an apparent pre-exponential value of 4.0x10 41 s −1 , both of which are, of course, nonsensical. 25 Further analysis based on differential scanning calorimetry (DSC) supported a reasonable interpretation for the observed results. It was shown that the steep slope of the rotational frequency vs. inverse temperature in the corresponding Arrhenius plot was the result of the structural softening that occurs when the 2D rigid glass becomes a 2D rotational fluid, during a second order glass transition.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…For example, when exploring the temperature-dependence of the rotational dynamics of a p -phenylene group in a periodic mesoporous organosilicate (PMO), we obtained non-linear data within a temperature region indicating an apparent activation energy of 47 kcal/mol and an apparent pre-exponential value of 4.0x10 41 s −1 , both of which are, of course, nonsensical. 25 Further analysis based on differential scanning calorimetry (DSC) supported a reasonable interpretation for the observed results. It was shown that the steep slope of the rotational frequency vs. inverse temperature in the corresponding Arrhenius plot was the result of the structural softening that occurs when the 2D rigid glass becomes a 2D rotational fluid, during a second order glass transition.…”
Section: Resultssupporting
confidence: 53%
“…24 Numerous previous studies with crystalline phenylene rotors have also revealed pre-exponential values of this magnitude, with exception encountered when non-crystalline samples are analyzed. 25 We have previously suggested that abnormally high pre-exponential factors in the solid state can be associated with changes in the fluidity of the structure, rather than with a static potential of the corresponding motions. For example, when exploring the temperature-dependence of the rotational dynamics of a p -phenylene group in a periodic mesoporous organosilicate (PMO), we obtained non-linear data within a temperature region indicating an apparent activation energy of 47 kcal/mol and an apparent pre-exponential value of 4.0x10 41 s −1 , both of which are, of course, nonsensical.…”
Section: Resultsmentioning
confidence: 99%
“…The pre-exponential factor, which can be interpreted as the barrier-less flipping rate of the pure phe-nylene bridge, 28,29 is 2.2×10 11 Hz and is somewhat smaller than those of phenylene bridges in related porous materials such as MOF-5 30,31 and periodically-ordered mesoporous organosili-ca. 22 It is conceivable, however, that intramolecular steric effects converge to decrease the pre-exponential factor in TPE derivatives relative to phenylene itself.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, while the [D 12 ]TCC2‐ R rate is comparable to other organic frameworks,27, 28, 29, 36 the very fast reorientation rate value obtained for the [D 12 ]TCC3‐ R is larger than in any exclusively organic systems reported previously below ≈200 K (Table S3) 18, 19, 24, 29, 32, 37, 38, 39. In particular, below this temperature, the dynamics of [D 12 ]TCC3‐ R are faster than the ones observed very recently for the para ‐phenylene reorientation in bis(sulfophenylethynyl)‐benzene frameworks based on an overall similar architecture of a phenylene molecular rotor sandwiched between two acetylene moieties (Figure 1 (b)), which previously showed the largest reorientation rate for porous organic materials to date 32…”
mentioning
confidence: 76%
“…The larger E a value obtained for [D 12 ]TCC2‐ R versus [D 12 ]TCC3‐ R is again consistent with stronger steric interactions in the terphenylene cage structure. The k 0 values obtained are on the low side of the ≈10 12  Hz22 value often associated with para ‐phenylene rotation, although these values vary significantly with the systems studied and k 0 in the 10 8 –10 41  Hz range are known 19, 23, 24, 27, 28, 29, 32, 36, 37, 40, 41. The associated change in entropy (Δ S ) is negative and is tentatively assigned to correlated rotational motion (Table S2) 41, 42…”
mentioning
confidence: 85%